Rotational Triboelectric Energy Harvester Utilizing Date-Seed Waste as Tribopositive Layer - Chilabi, Haider Jaafar; Abdullah, Luqman Chuah; Al-Ashtari, Waleed; As’arry, Azizan; Salleh, Hanim; Supeni, Eris E. (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
The growing need for self-powered Internet of Things networks has raised interest in converting abundant waste into reliable energy harvesters despite long-standing material and technology challenges. As demand for environmentally friendly self-powered IoT devices continues to rise, attention toward green waste as an eco-friendly energy source has strengthened. However, its direct utilisation in high-performance energy harvesters remains a significant challenge. Driven by the growing need for renewable sources, the triboelectric nanogenerator has emerged as an innovative technology for converting mechanical energy into electricity. In this work, the design, fabrication, and characterisation of a rotating triboelectric energy harvester as a prototype device employing date seed waste as the tribopositive layer are presented. The date seeds particles, measuring 1.2 to 2 mm, were pulverised using a grinder, mixed with epoxy resin, and subsequently applied to the grating-disc structure. The coated surface was machined on a lathe to provide a smooth surface facing. The performance of the prototype was evaluated through a series of experiments to examine the effects of rotational speed, the number of grating-disc structures, the epoxy mixing process, and the prototype’s influence on the primary system, as well as to determine the optimal power output. An increase in rotational speed (RPM) enhanced power generation. Furthermore, increasing the number of gratings and pre-mixing of epoxy with the biomaterial resulted in enhanced output power. Additionally, with 10 gratings, operating at 1500 rpm, and a 24 h pre-mixing method, the harvester achieved maximum voltage and power outputs of 129 volts and 1183 μW at 7 MΩ.